Associations between absolute and relative electronic cigarette harm perceptions and information‐seeking behaviours among US adult current, former and never smokers. (3rd August 2021) - Iles, Irina A.; Gillman, Arielle S.; Klein, William M. P.; Ferrer, Rebecca A.; Kaufman, Annette
Abstract: Introduction: Electronic cigarette (e‐cigarette) harm perceptions and information seeking behaviours are both important antecedents of e‐cigarette use, yet the relationship between them has been rarely studied. We assessed how absolute (e‐cigarettes are harmful to my health) and relative harm perceptions (e‐cigarettes are more/less harmful than cigarettes) were associated with specific e‐cigarette information seeking behaviours in a sample of current, former and never cigarette smokers. Methods: We used data from US adults in two cycles of the Health Information National Trends Survey (HINTS‐FDA 2015, n = 3738; 2017, n = 1736). Analyses controlled for socio‐demographics, ever e‐cigarette use and survey cycle. Data were analysed between January and August 2020. Results: Higher relative harm perceptions were associated with lower odds of having sought any information on e‐cigarettes [adjusted odds ratio 0.61, 95% confidence interval (0.48, 0.84)] and on how to use e‐cigarettes to quit smoking specifically [adjusted odds ratio 0.59, 95% confidence interval (0.38, 0.91)]. Smoking status did not moderate associations between absolute or relative harm perceptions and information seeking behaviours, nor was it associated with specific information seeking behaviours after adjusting for covariates. Discussion and Conclusions: The risks of e‐cigarettes relative to combusted cigarettes (as opposed to the absolute risks of e‐cigarettes) appear to be more important in individuals' information seeking behaviours about e‐cigarettes. Public health messages could ensure that all individuals understand how one's health risk would change if they exclusively used e‐cigarettes, switched to e‐cigarettes completely or used both products.